Conviction ebook - Mina, Denise (2019)
A true crime podcast sets a trophy wife's present life on a collision course with her secret past in this "blazingly intense" Reese Witherspoon book club pick and New York Times Best Crime Novel of the Year (A. J. Finn). The day Anna McDonald's quiet, respectable life exploded started off like all the days before: Packing up the kids for school, making breakfast, listening to yet another true crime podcast. Then her husband comes downstairs with an announcement, and Anna is suddenly, shockingly alone. Reeling, desperate for distraction, Anna returns to the podcast. Other people's problems are much better than one's own — a sunken yacht, a murdered family, a hint of international conspiracy. But this case actually is Anna's problem. She knows one of the victims from an earlier life, a life she's taken great pains to leave behind. And she is convinced that she knows what really happened. Then an unexpected visitor arrives on her front stoop, a meddling neighbor intervenes, and life as Anna knows it is well and truly over. The devils of her past are awakened — and they're in hot pursuit. Convinced she has no other options, Anna goes on the run, and in pursuit of the truth, with a washed-up musician at her side and the podcast as her guide. Conviction is "daredevil storytelling at its finest" (NPR's Fresh Air ), a breathtaking thriller from one of the most "superbly talented" writers of our time (Hank Phillippi Ryan, bestselling author of Trust Me ).